Case study of rain attenuation At 26 GHz in tropical region (Malaysia) for terrestrial link - Ulaganathen, Kesavan; Abdul Rahman, Tharek; Islam, Md. Rafiqul; Abdullah, Khaizuran (Institute of Electrical and Electronics Engineers Inc., 2016)
Millimeter wave (mm Wave) is today's breakthrough frontier for emerging wireless mobile cellular networks, wireless local area networks, personal area networks, and vehicular communications. In the near future, mm Wave products, systems, theories, and devices will come together to deliver mobile data rates thousands of times faster than today's existing cellular and WiFi networks for an example from the era of 3G towards 5G mobile communication near future. However for Tropical countries the data link reliability is effected during rain. This paper presents studies on rain attenuation at 26 GHz, which is widely used for local multipoint distribution service deployment by using the measured and prediction methods for terrestrial microwave links point to point in tropical regions. In this paper, discussion and comparison of five different reduction factor models have been presented. The essence of reduction factor is either to reduce the point rain rate to the path averaged rain rate, or to reduce the actual path length filled with the uniform point rainfall. Several models have been proposed by researchers to account for the horizontal variation of rain fall. However of ITU-R model, revised Moupfouma model, revised Silva Mello model and Lin model mostly been used for rain attenuation predictions in tropical regions. The Abdulrahman model is newly introduced has been take into consideration in this studies. The objective of these studies to identify most suitable rain attenuation prediction model for the Malaysian tropical region by comparing with actual measurement data at higher operating frequencies, such as 26 GHz which falls under Ka Band category. This study will provide useful information for researchers by understanding and good considerations in rain attenuation predictions for a terrestrial link operating frequency at 26 GHz in a tropical region. At the end of the analysis, it was found the Lin models predicts closely with the measurement value at 26 GHz with little error compare to other models.